Induksi Kalus Krisan (Chrysanthemum morifolium var. reagen pink) dengan Penambahan Naphtalen Acetic Acid (NAA) dan Kinetin Secara In-Vitro - Sholehah, Washeilatus; Resmisari, Ruri Siti; Oktafia, Safina; Mumpuni, Siwi Putri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Chrysanthemum morifolium var. reagent pink is an ornamental flower that is widely cultivated in Indonesia. The increasing demand makes it difficult for farmers to fulfill the market. In-vitro tissue culture is an effective solution to multiply chrysanthemum seedlings in bulk and quickly. This study aims to identify the most effective concentration in inducing callus in chrysanthemum plants by combining Naphtalen Acetic Acid (NAA) and kinetin. This study was an experimental research with a completely randomized design (CRD), involving 12 treatments and each treatment was repeated 4 times. There were two treatment factors; NAA concentration (0 mg/l, 0.5 mg/l, 1 mg/l) and kinetin concentration (0 mg/l, 1 mg/l, 2 mg/l, 3 mg/l). Parameters in this study included days to callus appearance, percentage of callus explants, callus wet weight, callus color, and callus texture. Data were analyzed using analysis of variance (ANOVA). The results showed that (1) the fastest callus was formed at 11 HST by giving the treatment of 0 mg/l NAA + 3 mg/l kinetin; (2) the optimal treatment for the percentage of callus explants was obtained by giving 1 mg/l NAA + 1 mg/l kinetin); (3) the optimal treatment of callus wet weight was obtained by giving 1 mg/l NAA + 2 mg/l kinetin; (4) the best callus quality was obtained by giving a combination of NAA 1 mg/l and kinetin 1 mg/l, with a crumbly texture and brownish yellow callus.